Z‐Transform Method for Pairwise Osteometric Pair‐matching1, 2. Issue 1 (14th May 2018) - Warnke‐Sommer, Julia D.; Lynch, Jeffrey James; Pawaskar, Sachin S.; Damann, Franklin E.
Abstract: A new pairwise osteometric pair‐matching approach based on the Z ‐transform method is presented. In contrast to previous methods that perform a global t ‐test on the summed skeletal element pair measurement distances, this approach performs t ‐tests on each individual distance, facilitating the capture of measurement‐specific variation. This new approach is compared to published pairwise sorting methods using a standard reference dataset of postcranial remains maintained by the Defense POW/MIA Accounting Agency. Receiver operating characteristic curve analysis indicates significantly improved performance for the clavicle and radius over all previous methods ( p < 0.01). The z ‐transform method weighted by the effect size outperformed the t ‐test (Byrd and Adams) and the mean t ‐test (Lynch) for all elements ( p < 0.01). The method performed better than the absolute value t ‐test (Lynch) for five elements ( p < 0.01) and performed at least as well for the remainder. To facilitate usability all methods are available at:https://github.com/spawaskar-cora/z-transform-method .